Assessment of alternative groundwater management options in sugarcane growing area in the Burdekin Delta, North Queensland - Qureshi, M E; Bajracharya, K; Qureshi, S E; Kirby, M (Australian journal of water resources, 2007)
Excessive irrigation has caused waterlogging in some parts of the Burdekin delta, while continued extraction of groundwater has reduced the hydraulic head of the aquifer and resulted in seawater intrusion. A groundwater management model was adapted to simulate the impact of various groundwater management strategies on waterlogging and seawater intrusion. The estimated areas subject to waterlogging and seawater intrusion, along with simulated data from a crop yield model, were used in a mathematical programming model to account for the economic impacts of the alternative groundwater management options in two neighbouring water board areas - North Burdekin Water Board (NBWB) and South Burdekin Water Board (SBWB) - in the Burdekin delta. The aggregate net revenues of all the management options are lower in the NBWB compared to the SBWB. In the NBWB, the aggregate net revenue is highest when groundwater use is also highest, while the aggregate net revenue is lowest when groundwater use is also lowest. In the SBWB, the aggregate net revenue is highest when groundwater use is relatively low and lowest when groundwater use is maximum.